Aquatic vascular plants of palo verde national park, Costa Rica (ESP) - Crow, Garrett E. (1986)
A study of the aquatic plants of palo Verde National park, Costa Rica, was undertaken during the rainy season of 1984. The swamp habitat is transitory, disappearing during the dry season, leaving only a few pools. The aquatic vegetation consists of a mosaic with emergent vegetation predominant with intermittent pools and lagunas, characterized by submersed and floating-leaved vegetation. Eleocharis mutatais the most important emergent. Other important plants include Thypha domingensis, Canna lutea and Thalia geniculata. Large patches of Neptunia plena and Aeschynomene sensitiva are also characteristic. In the pools Nymphaea ampla, Eichhornia crassipes, Heteranthera limosa and Najas guadelupensis are important.